New records of interaction between Pseudoxenos (Strepsiptera) and the solitary wasp Pachodynerus grandis in Brazil (Hymenoptera, Vespidae, Eumeninae) with an updated worldwide checklist of eumenine host species of Pseudoxenos - de Oliveira, Letícia A.; Barbosa, Lucas F. L.; de Oliveira, Luiz R.; Pereira, Matheus C. S. A.; Hermes, Marcel G. (Zootaxa, 2020)
Interactions between Strepsiptera (Pseudoxenos Saunders, 1872) and solitary wasps (Eumeninae) are recorded for the first time in Brazil for Pachodynerus grandis Willink & Roig-Alsina, 1998. An updated worldwide checklist of the host species of Eumeninae for Pseudoxenos is provided.